An in vitro method for studying subcellular rearrangements during cell polarization in Drosophila melanogaster hemocytes. (December 2018) - Edwards, Sandra Sofía; Delgado, María Graciela; Nader, Guilherme Pedreira de Freitas; Piel, Matthieu; Bellaïche, Yohanns; Lennon-Duménil, Ana María; Glavic, Álvaro
Abstract: Thanks to the power of Drosophila genetics, this animal model has been a precious tool for scientists to uncover key processes associated to innate immunity. The fly immune system relies on a population of macrophage-like cells, also referred to as hemocytes, which are highly migratory and phagocytic, and can easily be followed in vivo. These cells have shown to play important roles in fly development, both at the embryonic and pupal stages. However, there is no robust assay for the study of hemocyte migration in vitro, which limits our understanding of the molecular mechanisms involved. Here, we contribute to fill this gap by showing that hemocytes adopt a polarized morphology upon ecdysone stimulation, allowing the study of the cytoskeleton rearrangements and organelle reorganization that take place during the first step of cell locomotion. Highlights: Drosophila melanogaster hemocytes are a great tool for unraveling key aspects of immune cell migration. Drosophila plasmatocytes cultured under confinement were polarized but unable to migrate in vitro . We present a method to study in vitro hemocyte polarization to determine cytoskeletal and organellar rearrangements. Active rearrangement of actin and tubulin networks, together with myosin-II and Arp3 were observed in polarized hemocytes. Lysosomes localize to the rear of polarized hemocytes, mimicking cellular mechanisms of mammalian immune cell migration.